1996
DOI: 10.1111/j.1553-2712.1996.tb03349.x
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Sexually Transmitted Diseases in Women with Urinary Infections

Abstract: Objective: To determine the prevalence and factors associated with unrecognized sexually transmitted diseases (STDs) in women who had pelvic examinations and were subsequently released from the ED with a sole diagnosis of urinary tract infection (UTI). Methods: A 3‐month retrospective chart review was performed in an urban teaching hospital ED (>70,000 visits/year). Women aged 12–45 years who had pelvic examinations and were released from the ED with a sole diagnosis of UTI were included. Patient complaints, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 5 publications
4
29
1
Order By: Relevance
“…Our data show that 18% of sexually active women presenting to the ED with urinary tract infection complaints were found to have an STD. This adds support to the notion that STDs can be difficult to diagnose [2,5] and emphasizes the likelihood of misdiagnosis of STD because symptoms are often absent or easily misidentified as a simple urinary tract infection. , STDs continue to pose serious long term health consequences including pelvic inflammatory disease, infertility, ectopic pregnancy, salpingitis, and perinatal infections [4].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Our data show that 18% of sexually active women presenting to the ED with urinary tract infection complaints were found to have an STD. This adds support to the notion that STDs can be difficult to diagnose [2,5] and emphasizes the likelihood of misdiagnosis of STD because symptoms are often absent or easily misidentified as a simple urinary tract infection. , STDs continue to pose serious long term health consequences including pelvic inflammatory disease, infertility, ectopic pregnancy, salpingitis, and perinatal infections [4].…”
Section: Discussionsupporting
confidence: 53%
“…Back Pain 42% Hematuria 8% Comparisons between this prospective study (n=49), our previous retrospective study (n=60), and that of Berg et al [2] (n=94) is seen in Figure 2. Berg et al [2] examined females presenting to the ED with lower urinary complaints at a nearby but more urban locale hospital.…”
Section: Suprapubic Tenderness 70%mentioning
confidence: 73%
See 2 more Smart Citations
“…[7] While some other studies have shown an increase in CT or GC among women with urinary symptoms or UTI, others have not. [8] [9,10] The only prospective study of adolescent girls with urinary symptoms found that 29% had an STI (TV, GC, HSV, or CT), 23% had candida vaginitis, 17% had UTI, and an additional 17% had both UTI and vaginitis. [11] However, the sample size was small, there was no asymptomatic control group, and the testing methods in 1982 were less sensitive than those that are currently available.…”
Section: Discussionmentioning
confidence: 99%